Don't push the wrong button. The concept of microperspective in futures research - Virmajoki, Veli (wiley, 2025)
In this paper, we introduce the notion of a microperspective to futures research. Contrary to the more traditional timespans of futures research that are measured in years or decades, a microperspective focuses on shorter timespans that can be measured even in minutes. We point out that the use of a microperspective can provide an understanding of the central issues of futures research from a new angle. These issues involve the difficulties in estimating the future, the entanglement of the future with accounts of it, and the (in)ability to relate to certain futures. We argue that a microperspective can provide an understanding of how patterns shaping the future are created, how people respond to patterns, and how conflicts and misunderstandings shape the future. As an illustrative case, we discuss how the workings of elevators and the development of predictive algorithms in Kone corporation shape the future moment-by-moment in an interaction between the users and the developers. A microperspective shows how the different temporal orientations of the actors and their different interpretations of the environment interact. The case indicates that a microperspective can provide a novel way to study some of the central issues in futures research. The case also indicates that the notion of a microperspective is not merely an academic concept but has practical utility in planning and creating the future.